The Diversity of Lipopolysaccharide (O) and Capsular Polysaccharide (K) Antigens of Invasive Klebsiella pneumoniae in a Multi-Country Collection - Choi, Myeongjin; Hegerle, Nicolas; Nkeze, Joseph; Sen, Shaichi; Jamindar, Sanchita; Nasrin, Shamima; Sen, Sunil; Permala-Booth, Jasnehta; Sinclair, James; Tapia, Milagritos D.; Johnson, J. Kristie; Mamadou, Sylla; et al. (Frontiers in Microbiology, 2020)
Klebsiella pneumoniae is a common cause of sepsis and is particularly associated with healthcare-associated infections. New strategies are needed to prevent or treat infections due to the emergence of multi-drug resistant K. pneumoniae. The goal of this study was to determine the global diversity and distribution of O (lipopolysaccharide) and K (capsular polysaccharide) antigens on a large (>500) global collection of K. pneumoniae strains isolated from blood to inform vaccine development efforts. A total of 645 K. pneumoniae isolates were collected from the blood of patients worldwide during 2005-2017. O antigen types including the presence of modified O galactan types were determined by PCR. K types were determined by multiplex PCR and wzi capsular typing. Sequence types of isolates were determined by multilocus sequence typing (MLST) targeting seven housekeeping genes. Antibiotic susceptibility was determined using the Kirby-Bauer disk diffusion method. Among 645 isolates, four serotypes, O1, O2, O3 and O5, accounted for 90.1% of K. pneumoniae strains worldwide. Forty-nine percent of 75 tested O1 and O2 strains were gmlABC-positive, indicating the presence of the modified polysaccharide subunit D-galactan III. The most common K type was K2 by both multiplex PCR and wzi capsular typing. Of 39 strains tested by MLST, 36 strains were assigned to 26 known sequence types of which ST14, ST25 and ST258 were the most common. Among 591 isolates tested for antimicrobial resistance, we observed that 19.3% of isolates were non-susceptible to carbapenems and 62.1% of isolates were multidrug resistant (from as low as 16% in Sweden to 94% in Pakistan). Significantly more O1 isolates were multidrug resistant than non-multidrug resistant. Given the limited number of O antigen types, diverse K antigen types and the high multidrug resistance, we believe that an O antigen-based vaccine would offer an excellent alternative therapeutic strategy to prevent K. pneumoniae invasive infection.